Overlooked benefits of consumer credit growth: Impact on formal employment - Güneş A. Aşık (IZA Journal of Labor Policy, 2018)
This paper investigates the role of consumer credit growth and expansion of consumer financial services on the reduction of informal employment in a developing country. I argue that financial services growth should lead to a decline in the share of informal employment given that consumers whose borrowing constraints are relaxed are more likely to purchase goods with consumer credit and more likely to demand formal contracts. I test this hypothesis by exploiting the regional variation in consumer credit growth in Turkey. In order to address the endogeneity of financial services, I employ minority population loss between 1893 and 1935 in as an instrument. The identification strategy relies on the fact that minorities were main users of financial instruments as they were the trading class in the former Ottoman Empire. The results provide evidence in favor of a positive causal impact of consumer credit growth on formal employment, especially on low-skilled labor.
Keywords: D53; E26; F66; G21; G28; J08; J46; J48; 330; Informal employment; Consumer credits; Financial services